Web-based cognitive behavioral treatment for bulimia nervosa: a randomized clinical trial - Hartmann, Steffen; Timm, Christina; Barnow, Sven; Rubel, Julian; Lalk, Christopher; Prüßner, Luise (JAMA network open, 2024)
OBJECTIVE To evaluate the effectiveness of a web-based cognitive behavioral self-help intervention for individuals with BN. DESIGN, SETTING, AND PARTICIPANTS A 2-group randomized clinical trial without follow-up was conducted between February 2, 2021, and July 9, 2022, in Germany. Participants aged between 18 and 65 years who met the diagnostic criteria for BN were enrolled online via self-referral. Data analyses were conducted from October 24, 2022, to December 23, 2023. INTERVENTIONS A web-based cognitive behavioral self-help intervention including 12 weekly modules was compared with a waiting-list control group only having access to routine care. MAIN OUTCOMES AND MEASURES The primary outcome was the change in the number of bulimic episodes between baseline and posttreatment. Secondary outcomes included changes in global eating disorder symptoms, clinical impairment, well-being, work capacity, comorbid symptoms, selfesteem, and emotion regulation complemented by weekly measures and ecological momentary assessment. Intention-to-treat analyses were performed. - RESULTS Participants (N = 154; mean [SD] age, 29.6 [8.6] years; 149 [96.8%] female) receiving the web-based intervention demonstrated a significantly greater decrease in bulimic episodes compared with the control group (Cohen d = −0.48; 95% CI, −0.75 to −0.20; P < .001), representing a significant change in binge-eating episodes (Cohen d=−0.61; 95% CI, −0.89 to −0.33; P < .001), but not in compensatory behaviors (Cohen d = −0.25; 95% CI, −0.51 to 0.02; P = .21). The intervention was superior in improving global eating disorder symptoms (Cohen d=−0.61; 95% CI, −0.89 to −0.32; P < .001) and clinical impairment (Cohen d=−0.62; 95% CI, −0.92 to −0.33; P < .001). No significant effects were found for well-being (Cohen d=−0.08; 95% CI, −0.37 to 0.22; P > .99) and work capacity (Cohen d=−0.01; 95% CI, −0.68 to 0.66; P = .99). Exploratory analyses indicated significant changes in self-esteem and emotion regulation difficulties, but not in comorbid symptoms. - CONCLUSIONS AND RELEVANCE In this randomized clinical trial, a web-based cognitive behavioral self-help intervention effectively decreased eating disorder symptoms and illness-related burden in individuals with BN, underlining the potential of digital interventions to complement established treatments.
Gesehen am 19.11.2024
Keywords: Bulimie; Kognitive Verhaltenstherapie